Extent of surgery in chronic rhinosinusitis: primarily focused on nasal polyposis - Petr Schalek; Lukáš Otruba; Anasuya Guha (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Background: The prevalence of chronic rhinosinusitis with nasal polyps (CRSwNP) is estimated at around 4% in general population. The population-based studies using rhinoendoscopy have demonstrated the prevalence of nasal polyposis, with values ranging from 0.5 to 2.7%. If the symptoms and reduction in the quality of life persists despite adequate conservative therapy, then such patients are indicated for surgical treatment. This review aims to summarize existing literature and discuss the issue of the extent of the surgery in polyp disease.  Methods and Results: Forty-fi ve relevant articles were identifi ed using a multi-step search of the web-based PubMed database from the National Library of Medicine. These included articles published between January 1985 and December 2016 and separated into three categories according to surgical intervention: simple polypectomy, complete ESS vs. targeted procedures and extended procedures. The last category was further subdivided into 5 subgroups and discussed separately; namely: middle turbinate resection, radical ethmoidectomy (nasalisation), extended endonasal maxillary antrostomy, approaches through anterior wall of maxillary sinus and Draf 3 frontal sinusotomy.  Conclusion: Due to the considerable lack of randomised controlled trials for the surgical treatment, the optimal extent of surgery in CRSwNP has not been established yet. Although there are a number of studies dealing with surgical treatment of CRSwNP, and some data suggests that in cases of severe, diffuse or recurrent polypoid disease, better outcomes can be achieved by more extensive surgical approaches, unfortunately a great heterogeneity still exists amongst patients' characteristics, design of studies and disease severity thus making collection of high level of evidence still challenging.